(untitled) (Acta Scientiarum. Health Sciences, 2025)
Sleep is a physiological-rhythmic state characterized by the loss of consciousness and responsiveness, during which crucial processes for learning and metabolism occur. Therefore, maintaining adequate sleep quality is essential. The objective of this study was to describe the sleep quality of medical students in Paraguay during the first semester of 2024. A descriptive cross-sectional study was conducted on medical students in Paraguay. Data were collected using the Pittsburgh Sleep Quality Index (PSQI) and analyzed with IBM SPSS Statistics v.23 software. A total of 466 students participated, with an average age of 21.30 years (SD ± 3.08); and 58.8% were male. The majority resided in Asunción (54.7%). 51.1% reported poor subjective sleep quality, primarily first-year students (59.5%). Sleep latency difficulties were noted by 33.9% weekly, while 42.1% slept 5-6 hours, and 27% less than 5 hours. Sleep efficiency exceeded 85% for 59.9%, and 48.9% experienced monthly sleep disturbances. Only 25% used sleep medication, which positively affected sleep quality (p = 0.02). Daytime dysfunction affected 35.8%, mainly among sixth-year students. Overall, 64.4% had moderate sleep quality, 27.5% had poor sleep quality, and only 8.2% reported good sleep quality. Medical students in Paraguay presented moderate to poor sleep quality, with first-year students being the most affected.